Experiences of Anticipated and Enacted Pre-Exposure Prophylaxis (PrEP) Stigma among Latino MSM in Los Angeles - Brooks, Ronald A. (AIDS Behav, 2019)
Latino men who have sex with men (MSM) are a group critically affected by HIV. Pre-Exposure Prophylaxis (PrEP) is a biomedical prevention strategy that can help reduce new infections in this population. However, PrEP use may expose users to experiences of PrEP-related stigma. In-depth interviews conducted with Latino MSM PrEP users (N=29) were analyzed using thematic analysis to explore experiences of PrEP stigma. Six themes emerged related to anticipated and enacted PrEP stigma: (1) Perception that PrEP users engage in risky sexual behaviors; (2) PrEP-induced conflict in relationships; (3) Perception that PrEP users are HIV-positive; (4) Generational differences in attitudes toward HIV prevention; (5) Experiences of discomfort, judgment, or homophobia from medical providers; and (6) Gay stigma related to PrEP disclosure to family. Manifestations of stigma included disapproving judgment, negative labeling, rejection, and devaluing individuals. The social consequences associated with using PrEP may deter uptake and persistence among Latino MSM.